The importance of mediation in the development of entrepreneurial minds - Evelyn Veronica Almeida; Guido Vinicio Duque (Innova Research Journal)
The current unemployment of young adults in developing countries such as Ecuador is partially due to the collapse of the social security system, the increase in time of workers’ contributions to the retirement system, and the economic crisis. Assisting youth in creating their own labor market opportunities through developing entrepreneurial competencies is a possible partial remedy to the unemployement situation in the country. However, the main problem in establishing these competencies in business classes, where there is a gap between the theory of entrepreneurship and the simulation, and between the simulation and the entrepreneurial reality. To fill this gap, we are proposing a pedagogical model that merges students’ entrepreneurial traits and curiosities with guidance and experience from teachers and entrepreneurs to develop business projects, taking advantage of business opportunities to facilitate employability in the local area. This model draws upon Vygotsky’s (1978) concepts of Zone of Proximal Development and Mediation, Lantolf and Poehner´s (2011) concept of Dynamic Assessment, and Béchard and Toulouse´s (1991) Pedagogical Model in Entrepreneurship.